HUKUM DAN APLIKASI BAY‘ AL-‘ĪNAH MENURUT MAZHAB DAN ULAMA KONTEMPORER - Maulidizen, Ahmad (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2018)
Bay‘ al-‘īnah is a buying and selling contract that became the debate of classical and contemporary scholars in terms of law and its implementation. Therefore, it is necessary to have an article describing the concept of bay‘ al-‘īnah to determine the law of the bay‘ al-‘īnah. In this article the author will explain the concepts, laws and applications of bay‘ al-‘īnah according to contemporary schools and scholars by stating their reasons for choosing strong opinions. The fuqaha agree to forbid the bay‘ al-‘īnah if there is a condition that ma‘qud ‘alayh must be resold to the seller of origin. Likewise, if there is a hint of the existence of ḥīlah do the usury then the law also is void. What is fuqaha debate is that if there is no such requirement and no referent. In this case the authors hold that the bay‘ al-‘īnah contract is haram if the intention of doing usury is not stated in contract. However, the status of the contract is valid or not void as long as there is no requirement of mabī‘ to be resold to the original seller and the absence between the two parties who intend to do usury. This is because with the intention, although outside the contract then the intention of usury has been declared and can cancel the contract.